Nanoencapsulated Clove Oil Applied as an Anesthetic at Slaughtering Decreases Stress, Extends the Freshness and Lengthens Shelf Life of Cultured Fish - López‐Cánovas, Amanda Esperanza; Cabas, Isabel; Chaves-Pozo, Elena; Ros‐Chumillas, María; Navarro‐Segura, Laura; López‐Gómez, Antonio; Fernandes, Jorge Manuel de Oliveira; Galindo-Villegas, Jorge; García‐Ayala, Alfonsa (Foods, 2020)
In the aquaculture industry, fish are stunned using a wide range of methods, but all of them trigger stress responses and affect the fish flesh quality. Chilled water is considered one of the most efficient methods, but even this is not a stress-free experience for the fish. Anesthetics included in the ice slurry or in water could decrease this stress and delay the loss of flesh quality. In this work, we analyze the effect of clove oil (CO) nanoencapsulated in β-cyclodextrins (β-CD) (CO + β-CD), incorporated in the stunning bath, on the stress response and the organoleptic attributes of fresh marine and freshwater fish from four economically important fish species: Atlantic salmon, European seabass, Nile tilapia, and Rainbow trout. CO + β-CD reduces the time required to induce anesthesia, independently of water salinity, habitat or water temperature. The plasmatic glucose and cortisol levels decreased in all four species, although the concentrations of CO varied between species. Moreover, plasmatic lactate level differed between the marine and freshwater fish. The use of CO + β-CD extended the shelf life of fish from all the species studied (by 3–7 days). In conclusion, using CO encapsulated in β-CD for anesthetizing fish can be regarded as an improved fish-stunning technique that reduces the anesthesia-induction time, decreases the stress response, and extends the shelf life of fresh fish. publishedVersion